THE RESEARCH FOOTPRINT IN BRAND ATTITUDE: A BIBLIOMETRIC REVIEW BASED ON SCOPUS AND VOSVIEWER - Riyan Falah Al Wahid; Retno Widowati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study conducted a bibliometric mapping of the development of brand attitude research during the 2020–2025 period. Based on the analysis of 133 Scopus-indexed articles, the findings revealed a significant increase in publication volume, peaking in 2023. China, South Korea, India, and the United States were recorded as the most prolific contributors. Keyword network analysis identified that brand attitude formed a strong relationship with purchasing intention, brand loyalty, consumption behavior, and brand image. Furthermore, this study successfully uncovered the emergence of new research areas post-pandemic, such as femvertising, sustainability advertising, self-brand connection, and gamification, which represented a shift in trends in brand attitude studies in the digital era. This study complemented the limitations of previous bibliometric studies by presenting a more up-to-date and relevant mapping of contemporary consumer behavior.